Impact of referral guideline enforcement on orthopedic and trauma admissions at Kenyatta National Teaching and Referral Hospital, Kenya: A pre-post test design - Omondi, M.P.; Korir, Max; Owiti, O.J. (African Journals Online, 2023)
Background: The suboptimal utilization of tertiary health facilities and inadequate management of referral systems in low- and middle-income countries pose challenges to health system administration, characterized by frequent self-referrals and bypassing of lower-tier health facilities. On July 1, 2021, Kenyatta National Hospital (KNH) implemented referral guidelines, mandating that all admitted patients be referred from lower-tier health facilities, aligning with the KNH legal statute of 1987. This study aimed to evaluate the impact of enforcing referral guidelines on the spatial distribution of orthopedic and trauma admissions at KNH.